Comfort and religious-spiritual coping of intensive care patients’ relatives - Meneguin, Silmara [UNESP]; Pollo, Camila Fernandes [UNESP]; Benichel, Cariston Rodrigo [UNESP]; Cunha, Larissa Kazitani [UNESP]; Miot, Hélio Amante [UNESP] (My University, 2020)
Objectives: To identify the level of comfort and religious-spiritual coping of family members of intensive care unit patients and to analyse the sociodemographic/clinical variables that influence this association. Methods: Cross-sectional study on the adult and paediatric intensive care units of two public hospitals in the state of São Paulo, between January and September 2016. Participants were divided into two groups: adult (n = 96) and paediatric (n = 70). We used the religious-spiritual coping brief (RSC-Brief) and the comfort scale for relatives of people in critical states of health (ECONF). Results: Comfort was low in both groups and the family members used limited strategies in the RSC-Brief. The multiple linear regression analysis indicated that the variable length of hospitalization (β = 0.69; p < 0.01) influenced comfort and was also associated with the RSC-Brief (β = -0.18; p < 0.01). Conclusion: Family members’ comfort was low in both groups. It increased with the hospitalisation time of the patients' relative and tended to decrease with the severity of the disease.
Keywords: Family; Intensive Care Units; Nursing; Spirituality